ANTI-INFLAMMATORY ACTIVITY OF ETHANOL EXTRACT AND ETHYL ACETATE FRACTION OF KEBIUL (Caesalpinia bonduc L.) SEED COAT AGAINST INHIBITION OF PROTEIN DENATURATION - Dwi Fitriyani; Raden Fatahillah (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2022)
Inflammation is a normal protective reaction against tissue damage caused by physical injury, harmful chemicals, and protein denaturation. Protein denaturation is a process in which proteins lose their tertiary structure and secondary structure due to foreign substances, external compounds, such as strong acids, strong bases, organic salts, organic solvents, and heating. The purpose of this study was to determine the anti-inflammatory activity of ethanol extract and ethyl acetate fraction of the seed coat of Kebiul (Caesalpinia bonduc L.) by calculating the IC50 value of protein denaturation in the sample. The results of the phytochemical test of the ethanol extract of Kebiul seeds contained flavonoids, alkaloids, terpenoids, steroids, saponins, and tannins, while the ethyl acetate fraction only contained tannins and alkaloids. The results of the anti-inflammatory test showed that the highest percent inhibition value of sodium diclofenac, ethanol extract, and ethyl acetate fraction, respectively, at a concentration of 20 ppm was 84.8%; 84.1%; and 50%. The IC50 values ​​of sodium diclofenac, ethanol extract, and ethyl acetate fraction were 5.4 μg/mL; 9.9 μg/mL; and 13.3 μg/mL, respectively. The three samples had percent inhibition values exceeding 20% which indicated that all three can be used as an anti-inflammatory. Keywords: anti-inflammatory, protein denaturation, Caesalpinia bonduc L.